Early Changes in Visual Quality and Corneal Structure after DMEK: Does DMEK Approach Optical Quality of a Healthy Cornea?. (23rd September 2018) - Satue, Maria; Idoipe, Miriam; Gavin, Alicia; Romero-Sanz, Maria; Liarakos, Vasilios S.; Mateo, Antonio; Garcia-Martin, Elena; Blasco-Martinez, Alejandro; Sanchez-Perez, Antonio
Abstract : Purpose . To evaluate early changes in visual function and visual quality parameters after Descemet membrane endothelial keratoplasty (DMEK) and to compare the outcomes with healthy controls. Methods . Thirteen patients who underwent DMEK and 14 controls were evaluated. All subjects underwent visual function evaluation, including visual acuity under photopic and mesopic lighting conditions and contrast sensitivity (CSV) tests CSV 1000 and Pelli-Robson. Corneal parameters were assessed with Oculus Pentacam. Corneal mean keratometry (Km), corneal densitometry values, and low and high order aberrations (LOA and HOA) were recorded. In DMEK patients, all tests were performed before surgery and 1 and 6 months after surgery. Results . In patients who underwent DMEK, photopic visual acuity improved from 0.59 to 0.31 at 1 month (p = 0.013 ) and 0.13 at 6 months (p = 0.008 ); mesopic visual acuity and all contrast sensitivity values (both CSV and Pelli-Robson test) improved significantly in the first month (p < 0.005 ). A significant decrease was observed in corneal density in the 0–2 mm ring (from 43.83 to 35.60, p = 0.043 ) and mean posterior Km (from −5.84 to −6.80, p = 0.005 ) in the first month. Corneal HOAs and all corneal densities improved at 6 months after DMEK (p < 0.05 ). All visual function parameters and corneal aberrations remained lower and higher, respectively, compared with healthy controls (p < 0.05 ). Corneal densities were comparable with controls at 6 months after DMEK (p > 0.05 ). Conclusions . Patients undergoing DMEK present visual function improvement and a decrease in corneal density at 1 month after surgery. Decrease in corneal posterior HOAs can be observed at 6 months. However, visual function outcomes and corneal aberrations remained worse compared with healthy controls.